2023
DOI: 10.3390/nu15040998
|View full text |Cite
|
Sign up to set email alerts
|

ABCG5 and ABCG8 Are Involved in Vitamin K Transport

Abstract: ATP-binding cassette protein G5 (ABCG5)/ABCG8 heterodimer exports cholesterol from cells, while Niemann–Pick C1-like 1 (NPC1L1) imports cholesterol and vitamin K. We examined whether ABCG5/ABCG8 transports vitamin K similar to NPC1L1. Since high concentrations of vitamin K3 show cytotoxicity, the cytoprotective effects of ABCG5/ABCG8 were examined. BHK cells expressing ABCG5/ABCG8 were more resistant to vitamin K3 cytotoxicity than control cells, suggesting that ABCG5/ABCG8 transports vitamin K3 out of cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[150] The VDR agonist, 1,25-dihydroxyvitamin D3, counteracts muscle atrophy by enhancing the VDR/SIRT1/SIRT3 axis. [151] Therefore, vitamin D supplementation becomes a potential nutritional support strategy for muscle atrophy. [150,152,153] In addition, a series of animal studies have shown that nicotinamide riboside and vitamins B6 and C have the potential to reduce muscle atrophy and promote skeletal muscle growth and repair.…”
Section: Vitaminsmentioning
confidence: 99%
“…[150] The VDR agonist, 1,25-dihydroxyvitamin D3, counteracts muscle atrophy by enhancing the VDR/SIRT1/SIRT3 axis. [151] Therefore, vitamin D supplementation becomes a potential nutritional support strategy for muscle atrophy. [150,152,153] In addition, a series of animal studies have shown that nicotinamide riboside and vitamins B6 and C have the potential to reduce muscle atrophy and promote skeletal muscle growth and repair.…”
Section: Vitaminsmentioning
confidence: 99%
“…1C ). In addition, a recent study found that ATP-binding cassette protein G5 (ABCG5)/ABCG8, a heterodimer exporting cholesterol, participates in the excretion of VK from the intestines ( 16 ).…”
Section: Absorption Distribution and Metabolism Of Vkmentioning
confidence: 99%